2014
DOI: 10.1111/1469-0691.12640
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of microorganisms from positive blood cultures by MALDI-TOF mass spectrometry subsequent to very short-term incubation on solid medium

Abstract: Rapid identification of the causative microorganism is important for appropriate antimicrobial therapy of bloodstream infections. Bacteria from positive blood culture (BC) bottles are not readily available for identification by matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS). Lysis and centrifugation procedures suggested for direct MALDI-TOF MS from positive BCs without previous culture are associated with additional hands-on processing time and costs. Here, we descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
97
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(111 citation statements)
references
References 24 publications
11
97
1
2
Order By: Relevance
“…Several studies have shown that MALDI-TOF MS analysis of samples obtained directly from positive blood cultures can correctly identify 66% to 97% of aerobic and anaerobic organisms causing monomicrobial bacteremia (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). As in the current study, the best results have been obtained with Gram-negative organisms.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Several studies have shown that MALDI-TOF MS analysis of samples obtained directly from positive blood cultures can correctly identify 66% to 97% of aerobic and anaerobic organisms causing monomicrobial bacteremia (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). As in the current study, the best results have been obtained with Gram-negative organisms.…”
supporting
confidence: 54%
“…Implementation of MALDI-TOF MS in the microbiology laboratory in conjunction with antibiotic stewardship has been associated with earlier initiation of effective antimicrobial therapy and lower 30-day mortality in patients with bloodstream infections (3). This technology has also been applied to reduce turnaround times for identification of blood culture isolates directly from positive blood culture broths (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Various techniques have been assessed, generally involving lysis/centrifugation of blood culture pellets in preparation for analysis by MALDI-TOF MS.…”
mentioning
confidence: 99%
“…Identification of microorganisms from positive blood culture using of MALDI Sepsity per processing kit requires approximately 20 minutes and it does independent of species (6, 10,13,18,20,25,26,32,33). Batch processing added approximately 1 min per blood culture analyzed.Our estimated time to identify bacteria from the positive blood culture, of fixed automated system BD BACTEC Fx signal time to MALDI-TOF mass spectrometry identification time, is not an objective, it includes the blood smear preparation time by Gram staining, …”
Section: Discussionmentioning
confidence: 99%
“…But in comparison with other studies our estimated time correspond to with foreign laboratories (10).Some studies even describe MALDI-TOF mass spectrometry advantages compared to other direct methods to identify the bacteria from the blood, for example, using polymerase chain reaction and the latter method is limited by the high cost, not every species of microorganisms is determined in one study, in addition, it is enough difficult to realize in practic (28)(29)(30)(31).…”
mentioning
confidence: 88%
“…Al momento de la redacción de este artículo, sólo hemos encontrado un trabajo que aborda este enfoque metodológico (identificación de hemocultivo positivo mediante EM luego de un corto período de incubación en medio sólido), con resultados comparables a los obtenidos por nosotros 10 .…”
Section: Artículo Originalunclassified